2011
DOI: 10.3797/scipharm.1107-24
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Rapid and Validated LC Determination of Lopinavir in Rat Plasma and Its Application in Pharmacokinetic Studies

Abstract: Lopinavir is a new specific and potent HIV-1 protease inhibitor. A simple and rapid Reverse Phase High-Performance Liquid Chromatographic method using UV detection was developed and validated for the analysis of lopinavir in rat plasma under isocratic conditions. The method involves a single step protein precipitation technique. The detector response was linear over the concentration range of 250 to 4000 ng mL −1. High recovery ranging from 97.5 to 101.2 percent was obtained which precludes the use of internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
(21 reference statements)
0
18
0
1
Order By: Relevance
“…Post‐dosing, samples were collected at following time points: 0.17, 0.25, 0.5, 1, 2, 3, 4, 6, 8 and 12 h. These samples were further harvested for plasma by centrifuging at 4°C for 10 min at 650 g and then stored at −70°C until further analysis. A validated HPLC method, previously reported[23] from our lab for estimation of LPV in rat plasma matrix, was used to analyze the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Post‐dosing, samples were collected at following time points: 0.17, 0.25, 0.5, 1, 2, 3, 4, 6, 8 and 12 h. These samples were further harvested for plasma by centrifuging at 4°C for 10 min at 650 g and then stored at −70°C until further analysis. A validated HPLC method, previously reported[23] from our lab for estimation of LPV in rat plasma matrix, was used to analyze the samples.…”
Section: Methodsmentioning
confidence: 99%
“…All QC samples (LQC, MQC and HQC) were considered to be stable under different realistic storage conditions, with the values of accuracy (RE) and precision (RSD) in the acceptable range (RE within ±15%, RSD ≤ 15%). Very limited LPV stability data in rat plasma have been reported in previous studies and only included freeze–thaw, short‐term and autosampler stability experiments (Vats et al, 2011). To the best of our knowledge, this is the first report that covers full validation and stability of LPV in rat plasma according to FDA guidelines (Food and Drug Administration, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The individual plasma concentration–time profiles of LPV in three rats are shown in Figure 2, and mean plasma pharmacokinetic parameters obtained using non‐compartmental analysis are presented in Table 4. Limited number of preclinical pharmacokinetic studies following single intravenous bolus of LPV in rats have been reported (Kumar et al, 2004; Vats et al, 2011). The elimination t 1/2 (0.49 ± 0.01 hr) obtained in this study is shorter than the t 1/2 previously reported (0.82 ± 0.03 hr) using the HPLC‐UV method for the detection of LPV (Vats et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations